The Lynden Pindling Exhibit: the Man, the Dream, the Moment - Hinsey, Shananda Miller (International Journal of Bahamian Studies, 2015)
The Sir Lynden O. Pindling Room at the Harry C. Moore Library and Information Centre of The College of The Bahamas contains an exhibit of over 260 items, including personal effects, gifts, gowns, photographs, speeches and publications. The items included in this special exhibit space are resources that scholars, students and the public may use to research the legacy of the former prime minister and, by extension, the history of The Bahamas.